Factors determining player drop-out in Massive Multiplayer Online Games - Lebres, I. (2018)
A large number of people worldwide play free-to-play Massive Multiplayer Online Games (MMOGs) on a regular basis. Considering the significant amount of investment required in the early phases of game development, product managers aiming to quickly attract players deploy several in-game premium features which can be purchased by players willing to leverage their gaming experience. When the gap of advantage between premium and non-premium players is quite noticeable, it may lead to the lack of game fairness, resulting in players dropping out. This study aims at understanding the relevance of the drop-out factors that can be controlled by product managers, with an emphasis on game fairness when compared to other factors. A survey was sent to English-speaking communities of a MMOG. Results show that 53.9% of the variation in dropping-out is explained by the significant predictors analyzed: latency/performance issues, in-game features, community, service/support team and game fairness. Latency/performance issues and game fairness are the most relevant drop-out factors. By focusing on drop-out factors that can be controlled by product managers, this research contributes for decision making in the development of free-to-play MMOGs.